A new hybrid approach for conceptual design of sugar palm fibre-reinforced polyurethane composites for automotive anti-roll bar - Mohammad Taha, Mastura (2017)
In this thesis, the development process relating to the conceptual design of an automotive anti-roll bar made of sugar palm fibre reinforced thermoplastic polyurethane composites is presented. The conceptual design is performed with the consideration of five mechanical design elements, which are material, function, force, failure mode and geometry. Each of the elements is considered at the beginning of design process, which is assisted by several design tools. Initially, after the customers and environment requirements are identified, selection of materials is carried out using an integrated Analytic Hierarchy Process (AHP) and three-phase Quality Function Deployment for Environment (QFDE). In the final stage of material selections, the ranked materials are evaluated based on their environmental impact using the Eco Audit tool from the Cambridge Engineering Selector 2013 software. This new approach to material selection using QFDE is applicable for selecting suitable natural fibre and thermoplastic matrix for the composite automotive anti-roll bar. Here, the results showed that sugar palm fibre is the suitable natural fibre and thermoplastic polyurethane is the suitable matrix for the composite automotive antiroll bar. Next, function and failure modes for the automotive anti-roll bar are analysed using available tools in Theory of Inventive Problem Solving (TRIZ), which are Function Analysis Diagram (FAD) and Cause and Effect Chain Analysis (CECA) respectively. Improper function of each of the automotive anti-roll bars is identified through the implemented tool and the root cause of the problem is investigated through CECA, while force analysis is performed between the two analyses. Later, the problem is solved through geometry specification in generating the concept design by using the integrated tools TRIZ and Blue Ocean Strategy (BOS). Development of conceptual designs is performed through a Morphological Chart, where a combination of several design solutions has resulted in the development of 42 conceptual designs for a composite automotive anti-roll bar. The final concept design of a sugar palm fibre reinforced thermoplastic polyurethane composites automotive anti-roll bar is selected through AHP and the results showed that a concept design that consists of tapered arms reinforced with ribs at both bent areas is the most suitable. Strategic Canvas from BOS is presented at the final stage and it showed that the sugar palm fibre reinforced thermoplastic polyurethane composites automotive anti-roll bar is the best one, compared with the steel and carbon fibre-based automotive anti-roll bar with respect to the customers’ and environmental requirements. In a summary, design process of natural fibre composite-based automotive anti-roll bar should be incorporated with the principle of mechanical engineering design in order to properly obtain the design solution. The systematic and structured approach would prevent cost damage and save time and energy. In this study, the design process is limited at the conceptual design stage and further study need to be conducted for detail design where details simulation and experimental study should be carried out later.